Scedosporium Prolificans, An Unusual Cause of Frontal Abscess - Beena; Honappa, Sridhar; Ashok, Naik Shalini (Genes Review, 2016)
Scedosporium infections have become one of the most common cause of deep mold infections. It has also become a potentially dangerous causative agent of local and invasive infections in immunocompromised and occasionally in immunocompetent patients. It exhibits intrinsic resistance to many antifungals making the treatment difficult, thereby increasing the mortality. We present a case of an immunocompetent patient who came with a swelling on the left upper eyelid with a discharging sinus. A diagnosis of frontal lobe abscess was made and the mucopurulent discharge from the sinus was sent to the microbiology laboratory to know the etiology. The KOH wet mount of this discharge showed the presence of septate hyphal elements and the fungal culture yielded the growth of Scedosporium prolificans.The patient was treated with intravenous voriconazole to which he showed a favourable response.